The Role Of Abraham Maslow's Hierarchy Theory In Moderating The Relationship Between Learning Interest And Arabic Learning Outcomes - Widi Astuti; Bekti Faizah (STAI Masjid Syuhada Yogyakarta, 2023)
Penelitian ini bertujuan untuk menguji adanya keterkaitan antara minat belajar terhadap hasil belajar serta peran teori hierarki Abraham Maslow dalam memoderasi hubungan antara minat belajar dengan hasil belajar. Penelitian dilakukan di Madrasah Tsanawiyah Muhammadiyah Wates, Kulon Progo. Penelitian ini menggunakan metode kuantiatif dengan sampel sebanyak 146 responden sampel berstrata yaitu 51 siswa kelas VII, 55 siswa kelas VIII, dan 40 siswa kelas IX. Perolehan data dilakukan melalui kuesioner dengan 4 skala Likert modifikasi dan tes. Selanjutnya, data diolah menggunakan pengujian korelasi, regresi linier sederhana, dan MRA (Moderated Regression Analysis). Pada penelitian ini, minat belajar terbukti mempengaruhi hasil belajar secara positif dan signifikan pada angka signifikansi 0,001 dan r square sebesar 0,540. Berdasarkan bukti tersebut menunjukkan bahwa minat belajar mempengaruhi hasil belajar sebesar 54%. Sementara itu, teori hierarki Abraham Maslow terbukti dapat memperkuat hubungan antara minat belajar dengan hasil belajar pada signifikansi 0,001 dan angka r square sebesar 0,991 yang berarti teori hierarki Abraham Maslow dapat memperkuat hubungan antara minat belajar dengan hasil belajar menjadi 99,1%. Abstract this study aims to examine the relationships between interest in learning and learning outcomes and the roles of Abraham Maslow's hierarchical theory in moderating the relationships between interest in learning and learning outcomes . The research was conducted at Madrasah Tsanawiyah Muhammadiyah Wates, Kulon Progo. This study used a quantitative method with a sample of 146 respondents with a stratified sample , namely 51 students in class VII, 55 students in class VIII, and 40 students in class IX. data collection was carried out through a questionnaire with 4 modifications Likert scales and tests . Furthermore , the data is processed using correlation testing, simple linear regression , and MRA ( Moderated Regression analysis ). In this study, learning interest is proven to influences learning outcomes positively and significantly at a significance number of 0.001 and an r square of 0.540. based on this evidence shows that interest in learning affects learning outcomes by 54%. Meanwhile , Abraham Maslow's hierarchical theory is proven to b able to strengthen the relationships between learning interest and learning outcomes at a significance of 0.001 and an r squared number of 0.991, which means that Abraham Maslow's hierarchical theory can strengthen the relationships between learning interest and learning outcomes to 99.1%..